Pair Negotiation When Developing English Speaking Tasks - Ingrid Liliana Bohórquez Suárez; Mary Mily Gómez Sará; Sindy Lorena Medina Mosquera (HOW, 2011)
This study analyzes what characterizes the negotiations of seventh graders at a public school in Bogotá when working in pairs to develop speaking tasks in EFL classes. The inquiry is a descriptive case study that follows the qualitative paradigm. As a result of analyzing the data, we obtained four consecutive steps that characterize students’ negotiations: Establishing a connection with a partner to work with, proposing practical alternatives, refusing mates’ propositions, and making practical decisions. Moreover, we found that the constant performance of the process of negotiation provokes students to construct a sociolinguistic identity that allows agreements to emerge.